Harvesting behaviour of three central European rodents: Identifying the rodent pest in cereals - Heroldová, M. (Marta); Tkadlec, E. (Emil) (Crop Protection, 2011)
In central Europe, rodent damage in cereal crops is usually attributed to the common vole but these are caused by other rodents such as Apodemus mice as well. This raises a practical problem of identifying the rodent pests causing the damage to cereals at the time of harvest. To facilitate field differentiation between the damage caused by voles or mice, we conducted laboratory experiments in which the common vole, wood mouse and pygmy field mouse were presented with standing culms of wheat. Harvesting behaviour in these rodents differed strikingly. Wood mice first climbed and then cut down the culm at a height of about 20 cm. Pygmy field mice climbed to the top of the culm, harvesting only the ear. Voles cut the culm close to the ground leaving the stubble of about 8 cm in height. Our observations provide a quick and simple clue for identifying a causal rodent species in cereals and help in adopting a proper strategy for population management of a pest rodent.